Extended-spectrum beta-lactamases in poultry in Africa: a systematic review - Akeemat O. Ayinla; Ana L. P. Mateus (Frontiers Media S.A., 2023)
Extended-spectrum beta-lactamase (ESBL)-producing bacteria present a unique problem because of their ability to cause infections that are difficult to treat in animals and humans. The presence of ESBL-Escherichia coli (E. coli) in poultry raises a major public health concern due to the risk of zoonotic transfer via the food chain and direct contact with birds and the environment. This review aimed to determine the frequency of ESBL-producing E. coli and associated ESBL genes in poultry in Africa. Three databases (PubMed, ScienceDirect, and Web of Science) and predetermined websites were searched to identify scientific and grey literature. Studies (1582) were screened at title, abstract, and full-text levels. This review was registered with PROSPERO (CRD42021259872). Thirty-three studies were deemed eligible for this review. Phenotypic ESBL expression was confirmed in 22 studies (66.7%) with a wide range of colonization noted in sampled poultry (1 - 100%). The blaCTX-Mgene was the most commonly isolated with the variants blaCTX-M-1and blaCTX-M-15being the most predominant in North and West Africa respectively. ESBL-producing E. coli isolates are frequently detected in poultry in farms and slaughterhouses across Africa thereby posing a potential health risk to humans. The paucity of data however does not allow for inferences to be made about the true extent of ESBLs in poultry in Africa.